Pengalaman Wisatawan dalam Konsumsi Jamu Tradisional sebagai Produk Wellness Tourism di Yogyakarta: Pendekatan Memorable Tourism Experience - Azis Fitri Profita Aznam; Setya Mukti Mahanani (AKPARDA, 2025)
The growth of wellness tourism has encouraged the development of tourism products based on health and local cultural heritage. Traditional herbal drink known as jamu represents an Indonesian cultural asset with potential to support wellness tourism in Yogyakarta. This study aims to analyze tourist experiences in consuming traditional jamu as a culture-based health product. The research applies a descriptive quantitative approach using questionnaires based on seven dimensions of the Memorable Tourism Experience (MTE). The findings show that tourists have positive experiences when consuming jamu, reflected through enjoyment, physical refreshment, cultural engagement, and increased knowledge of traditional herbal drink. The presence of traditional jamu stalls and modern jamu cafés reflects sustainability and innovation in developing jamu as a culture-based wellness tourism product.